The drought and salinity intrusion in the Mekong River Delta of Vietnam: Assessment Report - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
As an impact of the ongoing El Niño Southern Oscillation (ENSO) phenomenon, severe drought and salinity intrusion has been occurring in Mekong River Delta (MRD) of Vietnam and has caused varying degrees of damage to agriculture, fisheries and the livelihoods of people in the region. On 15 March 2016, the Vietnamese government and the United Nations Development Programme (UNDP) organized a meeting with donors, international organizations and other partners to discuss joint efforts for drought response and recovery. Another meeting was presided by the Ministry of Agriculture and Rural Development (MARD) Minister Cao Duc Phat and the UN Resident Coordinator on 30 March 2016 to report on the recent rapid assessments of current natural hazards and call for immediate, medium- and long-term support from the international community. MARD recognizes that this crisis and its subsequent effects (e.g. inundation after the drought) will recur in the future, and that there is a need to prepare and plan for necessary response measures. In response to this urgent call, the CGIAR Centers operating in Vietnam, in collaboration with MARD, organized a joint field assessment in the MRD to have a first-hand observation and assessment of the effects of the drought and salinity intrusion currently experienced by the region. The CGIAR interventions recommended based on the assessment may support the short-, medium- and long-term planning in response to the impacts of climate change. The strength that the CGIAR could contribute is in downscaling some of the global data and analyses to Vietnam scenarios and forecasts for their planning, recommending climate-smart agriculture (CSA) options for integration in current and future donor/development interventions, and identifying opportunities in research for development (R4D) for future preparedness.